2020
DOI: 10.1039/c9ra10487a
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Au@TiO2 porous electrospun nanofibers for catalytic applications

Abstract: Catalytically active porous and hollow titania nanofibers encapsulating gold nanoparticles were fabricated using a combination of sol–gel chemistry and coaxial electrospinning technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…et al(171) reported a kind of catalytic active porous and hollow TiO 2 nanofiber coated with gold NPs by sol-gel chemistry and coaxial electrospinning. The resultant Au@TiO 2 porous hollow nanofibers show good catalytic activity and recyclability.…”
mentioning
confidence: 99%
“…et al(171) reported a kind of catalytic active porous and hollow TiO 2 nanofiber coated with gold NPs by sol-gel chemistry and coaxial electrospinning. The resultant Au@TiO 2 porous hollow nanofibers show good catalytic activity and recyclability.…”
mentioning
confidence: 99%
“…The small-sized photocatalysts tend to be trapped together in the effluent, which eventually reduces the number of remaining catalysts in the system. Catalysts reclamation procedures such as centrifugation [ 9 ], gravitational sedimentation [ 10 ], and filtration [ 11 ] are also required in order to collect the lost catalysts. In long-term application, this might have an impact on the operational cost and impede the overall performance as the recyclability of the photocatalysts are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Their large specific surface makes them well-suited for diverse applications such as filters, catalysts, bioengineering, tissue engineering, and wearables. [38][39][40][41] For in vivo applications, it is reasonable to use nontoxic or low-toxic solvents for processing, such as dimethyl sulfoxide (DMSO), and polymers which can be dissolved in it. [42] An ideal candidate is polyacrylonitrile (PAN), being unambiguously spinnable from DMSO and not showing cell toxicity.…”
Section: Introductionmentioning
confidence: 99%